Kreativitas Mahasiswa KKN UNRI Meriahkan 1 Muharram dan 17 Agustus Serta Penyuluhan Mencegah Stunting - Hasnah Faizah; Riski Alfalah; Andi Firdaus Yohaini; Selin Rosalina; Ega Anggraini; Nabilatuzzahwa Nabilatuzzahwa; Govin Taj Mukhti; Ratih Kumala Sari (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
Pulau Jambu village, located in Kampar Regency, Riau, Indonesia, has an area of 60.7 km2 and a population of around 3,254 people, with the majority adhering to Islam. This village is divided into four hamlets: Sungai Betung, Kampung Panjang, Kampung Baru, and Pulau Jambu. This article describes the four main pillars that form the essence of Indonesian people's lives in Pulau Jambu Village: the "Kukerta Bangun Kampung" program as a form of community service, a lively 1 Muharram celebration, outreach efforts about stunting, and the commemoration of independence on August 17.each of these elements reflects cultural identity, religious values, health challenges, and the spirit of patriotism in the village community. With a variety of activities that include Adhan, Recitation, Tahfidz competitions, as well as festive competitions on August 17, Pulau Jambu Village strengthens Indonesian unity and culture while overcoming the problem of stunting and improving people's welfare